A Study on Ultraviolet Protection of 100% Cotton Knitted Fabric: Effect of Fabric Parameters - C. W. Kan (The Scientific World Journal)
The effect of fabric parameters such as weight, thickness, and stitch density on the ultraviolet (UV) protection of knitted fabrics was studied. Different knitting structures such as plain, pineapple, lacoste, and other combinations of different knitting stitches of knit, tuck, and miss as well as half milano, full milano, half cardigan, full cardigan, 1 × 1 rib, and interlock were prepared. Experimental results revealed that weight was the most important factor that affected UV protection while thickness and stitch density were not the leading factor in determining UV protection.